Pandangan Apoteker dalam Penerapan e-Prescribing di Rumah Sakit dan Farmasi Komunitas : Literatur Review - Muhammad Zaini; Muliyani Muliyani; Nazhipah Isnani; Husin Husin (Politeknik Unggulan Kalimantan, 2023)
Electronic Prescribing is a system that utilizes information technology to replace or reduce the use of paper prescriptions in the process of prescribing medication to patients. The implementation of e-Prescribing poses significant challenges related to user readiness, facilities, and other factors. This study aims to determine the perspectives of hospital and community pharmacists on the implementation of e-Prescribing. The research design used in this paper is a literature review. The objects used in this study were taken from the results of research published in national and international journals. Articles were obtained from PubMed and Google Scholar using the keywords